Risk factors for intracerebral hemorrhage in small-vessel disease and non-small-vessel disease etiologies—an observational proof-of-concept study - Arndt, Philipp; Chahem, Christian; Luchtmann, Michael; Kuschel, Jan-Niklas; Behme, Daniel; Pfister, Malte; Neumann, Jens; Görtler, Michael; Dörner, Marc; Pawlitzki, Marc; Jansen, Robin; Meuth, Sven G.; et al. (Frontiers in Neurology, 2024)
Background: Sporadic cerebral small vessel disease (CSVD), i.e. hypertensive arteriopathy (HA) and cerebral amyloid angiopathy (CAA), is the main cause of spontaneous intracerebral hemorrhage (ICH). Nevertheless, a substantial portion of ICH cases arises from non-CSVD etiologies, such as trauma, vascular malformations and brain tumors. While studies compared HA-and CAA-related ICH, non-CSVD etiologies were excluded from these comparisons and are consequently underexamined with regard to additional factors contributing to increased bleeding risk besides their main pathology.Methods: As a proof of concept, we conducted a retrospective observational study in n = 922 patients to compare HA, CAA and non-CSVD related ICH with regard to factors that are known to contribute to spontaneous ICH onset. Medical records (available for n = 861) were screened for demographics, antithrombotic medication and vascular risk profile and CSVD pathology was rated on magnetic resonance imaging (MRI) in a subgroup of n = 185 patients. The severity of CSVD was assessed with a sum score ranging from 0 to 6, where a score ≥ 2 was defined as advanced pathology.Results: In 922 patients with ICH (median age 71 years), HA and CAA caused the majority of cases (n = 670, 73%); non-CSVD etiologies made up the remaining quarter (n = 252, 27%). Individuals with HA-and CAA-related ICH exhibited a higher prevalence of predisposing factors compared to those with non-CSVD etiologies. This includes advanced age (median age: 71 vs. 75 vs. 63 years, p < 0.001), antithrombotic medication usage (33% vs. 37% vs. 19%, p < 0.001), prevalence of vascular risk factors (70% vs. 67% vs. 50%, p < 0.001) and advanced CSVD pathology on MRI (80% vs. 89% vs. 51%, p > 0.001). However, notably half of non-CSVD ICH patients were either aged over 60 years, presented with vascular risk factors or had advanced CSVD on MRI.Risk factors for spontaneous ICH are less common in non-CSVD ICH etiologies than in HA-and CAA-related ICH, but are still frequent. Future studies should incorporate these factors besides the main pathology to stratify an individual's bleeding risk.